Données sur la situation de la maladie de l'huître plate, Ostrea edulis L. - Grizel, Henri; Tige, Gilbert; Rabouin, Marie-agnès (Actes CIEM, CM 1976/K : 18, 1976)
Throughout the years 1974-1975, the flat oyster (Ostrea edulis Linné) disease has gradually spread to most of the French oyster culture centres and caused very important losses in farmed oysters and natural deposits. This note analyses the current evolution of the epizooty; to do so, we differentiate three types of flat oyster culture centres: Centres affected in the past by the epizooty and where the traditional flat oyster culture has become uncertain. It has been replaced by the culture of Crassostrea gigas and by the finishing, for 7 to 8 months, of flat oysters aged 3 or 4 years old which remained of good quality. Centres recently touched by the epizooty where the culture of flat oysters (18 months and 2 years old) from unharmed spat is still possible after the dredging of the parasited natural deposits. Uncontaminated centres that need to be protected from the possible arrival of parasited oysters. Au cours des années 1974-1975, la maladie de l'huître plate, Ostrea edulis Linné, a peu à peu gagné la majorité des centres ostréicoles français et provoqué des pertes très importantes tant sur les huîtres d'élevage que sur les gisements naturels. Cette note analyse l'évolution actuelle de l'épizootie elle distingue pour cela trois types de centres d'élevage de l'huître plate : les centres anciennement touchés par l'épizootie où la culture traditionnelle de l'huître plate est devenue aléatoire. Elle est remplacée par celle de Crassostrea gigas et par l'affinage, pendant 7 à 8 mois, d'huîtres plates de 3 ou 4 ans qui restent de bonne qualité. Les centres récemment atteints par l'épizootie où, après dragage des bancs naturels parasités, l'élevage d'huîtres plates (18 mois et 2 ans) à partir de naissain indemne est encore possible. Les centres non contaminés qu'il convient de préserver contre l'éventuel apport d'huîtres parasitées.